Entre ausências e pertencimentos: uma composição cartográfica do corpo negro nas fotografias das placas de formatura no espaço universitário - Mendes, Lucas Ribeiro (2023)
The public space in Brazil was constituted and grounded by many racist visual actions throughout our history. Teaching and learning spaces often also became a territory of reproduction and proliferation of racism. This dissertation presents a cartographic research that seeks, firstly, to map historically established social spaces, from a look aimed at investigating the presence of black people in these places, to subsequently propose a deterritorialization of an escape route, the subversion and desecration of racist devices, in the construction of a new territory from the questions posed. In this case, we seek to understand how the photographs present in the graduation plates arranged in the public space of the Federal University of Paraíba, more specifically of students of the Law course of the campus of the city of Santa Rita, affect the collective memory of black people in the university space. In addition to image analysis, the methodology of this research includes the teaching of a decolonial photography workshop and the writing of a field diary. The objectives are: (i) to carry out a documentary survey about the history of the black population in its relationship with the university environment in Brazil; (ii) to understand what makes up the photographic game of graduation plates; (iii) to conduct a decolonial photography workshop; (iv) propose an intervention in the territory of the university taking into account the affections and subjectivities of black people who attend there. Soulages (1998), Sontag (2004), Dubois (1994), Deleuze & Guattari (2015, 2012, 2011), Almeida (2017), Halbwachs (1977) Kilomba (2019), among others will compose the path of cartography. Articulation of the photographic issues with the issues of belonging, race, memory and affections have been made seeking to decipher what is hidden in the cracks, in the infotographable and silences.